Chronic limb threatening ischemia and diabetes mellitus: the severity of tibial atherosclerosis and outcome after infrapopliteal revascularization - Koivunen V; Juonala M; Mikkola K; Hakovirta HH (Sage, 2022)
Background and aims: Diabetes mellitus associates with poor outcomes in chronic limb threatening ischemia but data on different hypoglycemic regimens and outcomes are lacking. We analyzed insulin-treated diabetes mellitus, non-insulin-treated diabetes mellitus, and patients without diabetes mellitus.
Materials and methods: All patients with peripheral artery disease and/or diabetes mellitus and infrapopliteal revascularization in the Department of Vascular Surgery, Turku University Hospital during 2007-2015 were included. Tibial atherosclerosis was categorized into crural index classes of I-IV.
Results: Of the 497 patients, 180 were insulin-treated diabetes mellitus, 94 non-insulin-treated diabetes mellitus, and 223 patients without diabetes mellitus groups (diabetes mellitus 55.1%). Insulin-treated diabetes mellitus was the most ill, youngest (insulin-treated diabetes mellitus-median: 72.4, interquartile range: 64.0-79.5 versus non-insulin-treated diabetes mellitus-76.0, interquartile range: 67.9-83.6 versus patients without diabetes mellitus-77.3, interquartile range: 68.5-83.7, p < 0.001), had the highest body mass index (insulin-treated diabetes mellitus-median: 27.7, interquartile range: 24.0-31.8 versus non-insulin-treated diabetes mellitus-26.3, interquartile range: 23.2-30.3 versus patients without diabetes mellitus-23.9, interquartile range: 21.5-26.9, p < 0.001), and Charlson comorbidity index (insulin-treated diabetes mellitus-65.6% versus non-insulin-treated diabetes mellitus-46.8% versus patients without diabetes mellitus-10.8%, p < 0.001). After endovascular revascularization, limb salvage was poorer for insulin-treated diabetes mellitus (p = 0.046) and non-insulin-treated diabetes mellitus groups (p = 0.011) compared to surgery, but not for patients without diabetes mellitus (p = 0.15). Patients with crural index IV in insulin-treated diabetes mellitus (p = 0.001) and non-insulin-treated diabetes mellitus (p = 0.013) had higher mortality after revascularization. Crural index IV was a risk factor for limb loss (hazard ratio: 1.37, 95% confidence interval: 1.08-1.74, p = 0.008).
Conclusion: Limb salvage after bypass is better for insulin and non-insulin diabetics, compared to the endovascular approach. Extensive tibial atherosclerosis is an independent risk factor for limb loss. It associates with increased mortality in both insulin and non-insulin diabetics.